Potential mechanisms of acupuncture for neuropathic pain based on somatosensory system - Ma, Xin; Chen, Wen; Yang, Na-Na; Wang, Lu; Hao, Xiao-Wan; Tan, Chun-Xia; Li, Hong-Ping; Liu, Cun-Zhi (Frontiers in Neuroscience, 2022)
Neuropathic pain, caused by a lesion or disease of the somatosensory system, is common and distressing. In view of the high human and economic burden, more effective treatment strategies were urgently needed. Acupuncture has been increasingly used as an adjuvant or complementary therapy for neuropathic pain. Although the therapeutic effects of acupuncture have been demonstrated in various high-quality randomized controlled trials, there is significant heterogeneity in the underlying mechanisms. This review aimed to summarize the potential mechanisms of acupuncture on neuropathic pain based on the somatosensory system, and guided for future both foundational and clinical studies. Here, we argued that acupuncture may have the potential to inhibit neuronal activity caused by neuropathic pain, through reducing the activation of pain-related ion channels and suppressing glial cells (including microglia and astrocytes) to release inflammatory cytokines, chemokines, amongst others. Meanwhile, acupuncture as a non-pharmacologic treatment, may have potential to activate descending pain control system via increasing the level of spinal or brain 5-hydroxytryptamine (5-HT), norepinephrine (NE) and opioid peptides. And the types of endogenously opioid peptides was influenced by electroacupuncture-frequency. The cumulative evidence demonstrated that acupuncture provided an alternative or adjunctive therapy for neuropathic pain.